PERSEPSI PELAJAR WANITA MEMILIH KURSUS BINAAN BANGUNAN DI FPTV DARI ASPEK DORONGAN KELUARGA DAN RAKAN SEBAYA - Ariffin, Arihasnida; Abdul Manan, Nora Sakila; Rubani, Siti Nur Kamariah; Hamzah, Norhasyimah; Subramaniam, Tamil Selvan (Online Journal for TVET Practitioners, 2018)
This study aimed to identify the perception of female students chooses courses in Building Construction at Faculty of Technical and Vocational Education, Universiti Tun Hussien Onn Malaysia (UTHM) through aspect of family and peer encouragement. The study design used was a quantitative survey. The instrument used was in the form of a questionnaire distributed to female students of building construction course at the Faculty of Technical and Vocational Education, UTHM. A total of 158 respondents which is representing the total population selected for this study. Questionnaires used contain 23 items those are measured using a Likert Scale and analyzed using the Statistical Package for the Social Science (SPSS 21.0). Data analysis using descriptive statistics that include mean and percentage. The finding show that the highest value mean is the aspect of family support with value (4.26), while the peer group value is (3.78). The results obtained show that the family is the primary perception of respondents chose the course. This is because of the attitude of the family generally is the most important factor in the development of a student and the student influence in the selection of courses of study. The study suggests the conviction and attitudes of the female student teaching of practical courses Building Construction.